Journey to Plum Creek - Cuate, Melodie A. (Lubbock : Texas Tech University Press, 2012)
"Hannah, Nick, and Jackie time-travel to Texas in 1840. Taken captive by Comanche warriors, Hannah and Jackie experience Comanche life and participate in the Linnville raid; Nick meets Bigfoot Wallace and the Texas Rangers, who pursue the Comanche party until the two groups clash in the Battle of Plum Creek"--Provided by publisher.
Keywords: Wallace, Big-Foot, -- 1817-1899 -- Juvenile fiction; Wallace, Big-Foot, -- 1817-1899 -- Fiction; Texas Rangers -- Fiction; Comanche Indians -- Fiction; Indians of North America -- Fiction -- Texas; Indian captivities -- Fiction; Frontier and pioneer life -- Fiction -- Texas; Time travel -- Fiction; Texas -- Juvenile fiction -- History -- To 1846; Texas -- Fiction -- History -- To 1846